Material applied to automobile foot mat and preparation method of material
By using TPE, modified resin and modified nanopowder in automotive foot pad materials, a dense gel network is formed, which solves the problems of insufficient high temperature stability, aging resistance and waterproofness, and achieves excellent mechanical and waterproof performance. Meet the needs of modern consumers.
Patent Information
- Application Number
- CN202411411787.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
AI Technical Summary
The existing automotive foot pad materials have shortcomings in high temperature stability, aging resistance and water resistance, which limits their wider application.
TPE material is used with modified resin and modified nanopowder to guide the extended dispersion of nanopowder through long-chain and multi-branched structures to form a dense gel network, enhance mechanical properties and waterproof properties, and modify them through surface groups. Improve compatibility and hydrogen bonding forces, and reduce the activity of active molecules in high temperature environments.
It significantly improves the mechanical, wear-resistant, waterproof and aging resistance of automotive foot pad materials, meets the high-performance demand of modern consumers for interior foot pad materials, and has excellent market prospects.
Smart Images

Figure BDA0005078207940000161 
Figure BDA0005078207940000171
Abstract
Description
Technical Field
[0001] The present application relates to the field of automotive interior products, and in particular to a material for automotive floor mats and a preparation method thereof. Background Art
[0002] As an important accessory in the interior of a vehicle, the main function of car floor mats is to protect the vehicle carpet from daily wear, stains and moisture, while providing passengers with a comfortable touch and non-slip safety. With the popularization of automobile culture and the advancement of technology, floor mat materials have evolved from traditional natural materials to modern synthetic materials. Each generation of materials attempts to solve the problems of the previous generation and improve the user experience.
[0003] Early car floor mats were mostly made of materials such as blankets, woolen cloth or rubber. Although these materials can provide basic protection, they often have problems such as poor wear resistance, difficulty in cleaning, easy to mold or emit odor. With the development of synthetic material technology, PVC, synthetic rubber, synthetic fibers, etc. have been widely used because of their durability and high cost-effectiveness, and can effectively block moisture and dirt. However, PVC materials may release harmful substances at high temperatures, rubber materials sometimes have a strong irritating odor, and synthetic fibers have poor waterproof and anti-slip properties. All three have obvious material performance disadvantages, which limits their wider application.
[0004] As a new type of environmentally friendly material, TPE (thermoplastic elastomer) has emerged in the field of car mats in recent years. TPE combines the easy processing of plastics with the elasticity of rubber, and has excellent wear resistance and crack resistance. It is non-toxic and odorless, meeting the high standards of modern consumers for in-car air quality.
[0005] Although the application of existing TPE materials in car mats has shown many advantages, it still faces some challenges. For example, the high temperature stability, aging resistance and waterproof properties of TPE materials need to be strengthened as much as possible. Therefore, in order to solve the above problems, the present application provides a material for car mats and a preparation method thereof. The car mat material prepared by the present application has excellent mechanical and wear resistance while ensuring good high temperature stability, aging resistance, corrosion resistance and waterproof properties, which can meet the performance requirements of modern consumers for car mat materials and has a very excellent market prospect. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a material for automobile floor mats, which comprises, by weight, 40 to 60 parts of TPE, 10 to 25 parts of copolymer composition, 10 to 15 parts of modified resin, 10 to 25 parts of modified nanopowder, 1 to 2.5 parts of lubricant, 4 to 12 parts of dispersant, 0.5 to 1.5 parts of coupling agent, and 10 to 20 parts of additive.
[0007] As a preferred solution, the mass ratio of the TPE, copolymer composition and modified resin is (5-5.5): (1.5-2): (1.2-1.5).
[0008] As a preferred solution, the mass ratio of the TPE, copolymer composition and modified resin is 5.2:1.8:(1.2-1.4).
[0009] As a preferred solution, the mass ratio of the TPE, modified nano powder and dispersant is (5-5.5): (1.5-2.2): (0.6-1).
[0010] As a preferred solution, the mass ratio of the modified nano powder to the dispersant is 5.2:2:0.8.
[0011] As a preferred solution, the TPE is at least one of SEBS, SBS, SIS, and TPUs.
[0012] As a preferred solution, the TPE is SEBS.
[0013] As a preferred solution, the weight average molecular weight of the SEBS is 60,000-120,000.
[0014] As a preferred solution, the weight average molecular weight of the SEBS is 80,000-110,000.
[0015] As a preferred solution, the copolymer composition is a composition of polypropylene and polycarbonate.
[0016] As a preferred solution, the mass ratio of polypropylene to polycarbonate is (3-4): (0.5-1.5).
[0017] As a preferred solution, the mass ratio of the polypropylene to the polycarbonate is (3-3.5):(0.6-1).
[0018] As a preferred solution, the melt index of the polypropylene is 1.5-3 g / 10 min, and the test conditions are: 230° C. / 2.16 kg.
[0019] As a preferred solution, the melt index of the polycarbonate is 15-20 g / 10 min, and the test conditions are: 260° C. / 2.16 kg.
[0020] As a preferred solution, the preparation method of the modified resin comprises the following steps: S1: adding 2-ethylhexyl acrylate, methyl acrylate and hydroxyethyl acrylate to an organic solution, introducing nitrogen, adding an initiator, and heating to 65-80°C to react and generate a prepolymer; S2: mixing the prepolymer with acrylamide, adding a mixed solvent of deionized water and methanol and adding the initiator again, and after nitrogen fully replaces the reaction system gas, heating to 80-95°C and keeping the temperature for reaction for 5-8h to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the modified resin solution.
[0021] As a preferred solution, the mass ratio of 2-ethylhexyl acrylate, methyl acrylate, hydroxyethyl acrylate and acrylamide is (3-5): (6-10): (1-2): (20-30).
[0022] As a preferred solution, the mass ratio of 2-ethylhexyl acrylate, methyl acrylate, hydroxyethyl acrylate and acrylamide is (3-4): (8-9): (1-1.5): (20-25).
[0023] As a preferred solution, the organic solution is an acryloyl chloride solution.
[0024] As a preferred solution, the initiator is ammonium persulfate or potassium persulfate.
[0025] In this application, by adding the above modified resin, the mechanical, aging resistance, waterproof and high temperature stability of the car mat material can be greatly improved. After the modified resin is added to the mat material system, it can play a good guiding role on the added modified nano powder through its long chain and multi-branched structure, greatly improving the extension and dispersion effect of the nano powder in the system, and increasing the steric hindrance between active molecules, greatly delaying the excessive aggregation between them, thereby effectively enhancing the construction strength of the internal system network, forming a dense gel network, and when water molecules and external active molecules penetrate, their movement rate can be greatly reduced, and the contact frequency between them is reduced, thereby playing an excellent waterproof and aging resistance during long-term use, and enhancing the mechanical strength of the system through a dense network structure, and greatly reducing the activity of active molecules in a high temperature environment.
[0026] As a preferred solution, the preparation method of the modified nano powder comprises the following steps: S1: adding silicon dioxide and talcum powder to a DMF solution, adding succinic anhydride and a silane coupling agent, heating to 60-70°C for a 4-5h heat preservation reaction, filtering, washing, drying and taking out the product after the reaction is completed to obtain composite particles; S2: adding the composite particles and zinc acetate to a mixed solution of methanol and deionized water, then heating to 60-70°C and dropwise adding a methanol solution of dimethylimidazole for 1-1.2h, and then heat preservation for a 2-4h reaction; S3: adding acetic acid, ethanol and dicyclopentadiene after the reaction is completed, heating to 75-85°C and continuously stirring for a reaction of 8-12h, and after completion, centrifuging and filtering the product, and vacuum drying to obtain the product.
[0027] As a preferred solution, the mass ratio of the silicon dioxide, talc, succinic anhydride and silane coupling agent is (1-1.5): (4-4.5): (1.2-1.5): (0.3-0.5).
[0028] As a preferred solution, the mass ratio of the composite particles, zinc acetate, dimethylimidazole and dicyclopentadiene is (3-3.5): (1.5-2): (1-1.2): (0.3-0.6).
[0029] As a preferred solution, the average particle size of the talc powder is 0.1-0.3 μm.
[0030] As a preferred solution, the average particle size of the silicon dioxide is 20 to 50 nm.
[0031] As a preferred solution, the silane coupling agent is 3-glycidyltrimethoxysilane.
[0032] The modified nano powder added in this application can greatly improve the mechanics, temperature resistance, waterproofness and aging resistance of the car mat material. The modified nano powder added can greatly improve the compatibility and binding between the composite particles and the TPE system through the modification of the surface group, and through the hydrogen bonding force and van der Waals force between the surface group and the internal system, thereby playing an excellent group connection role while forming the powder micropores, thereby playing a good internal connection support when the external force acts; on the other hand, under the joint action of the modified resin, the modified nano powder strengthens its own paving and extension effect inside the system, so that on the surface of the material and when the material is used, a more flat surface is formed, and the overall content of the surface resin material is increased, and the flat and low surface energy surface can greatly reduce the formation speed of the hydration layer on the surface of the material and the integrity of the hydration layer, and then can maintain excellent waterproofness and aging resistance under the influence of a long moisture environment.
[0033] As a preferred solution, the lubricant is at least one of zinc stearate, magnesium stearate, calcium stearate, cyclohexane oil, paraffin oil, silicone oil, and white mineral oil.
[0034] As a preferred solution, the lubricant is white mineral oil or naphthenic oil.
[0035] As a preferred solution, the dispersant is a composition of epoxy block polyether and C13-C14 isomeric fatty alcohol polyoxyethylene ether.
[0036] As a preferred solution, the mass ratio of the epoxy block polyether to the C13-C14 isomeric fatty alcohol polyoxyethylene ether is (2-2.6):(4-4.5).
[0037] As a preferred solution, the mass ratio of the epoxy block polyether to the C13-C14 isomeric fatty alcohol polyoxyethylene ether is (2.2-2.4): (4.2-4.5).
[0038] As a preferred solution, the hydroxyl value of the C13-C14 isomeric fatty alcohol polyoxyethylene ether is 180-210 mgKOH / g.
[0039] As a preferred solution, the weight average molecular weight of the epoxy block polyether is 2000-3200.
[0040] As a preferred solution, the coupling agent is a titanate coupling agent.
[0041] As a preferred solution, the auxiliary agent at least includes a flame retardant, a plasticizer and an antistatic agent.
[0042] As a preferred solution, the mass ratio of the flame retardant, plasticizer and antistatic agent is (5-6): (8-10): (1.5-2).
[0043] As a preferred solution, the flame retardant is at least one of magnesium hydroxide, aluminum hydroxide, and phosphate ester.
[0044] As a preferred solution, the plasticizer is at least one of DOTP, DINP, polyethylene glycol sebacate, and phosphate esters.
[0045] As a preferred solution, the antistatic agent is an ethoxylated fatty amine.
[0046] The second aspect of the present application provides a preparation method for the above-mentioned material for automobile floor mats, and the preparation method comprises the following steps: S1: weigh all the required raw materials for use, then add TPE, copolymer composition, modified resin, lubricant and coupling agent into a stirring pot, and stir and mix at a low speed of 40-80rpm for 40-60min; S2: add the remaining raw materials, increase the speed to 150-200rpm and stir for 1.5-2h, add the mixed material after stirring to a twin-screw extruder for extrusion and plasticization, and the extrusion temperature is 200-240°C; S3: water-cooling and granulating the extruded material, sieving and screening, and ventilation and drying in sequence to obtain the obtained material.
[0047] The beneficial effects of this application are:
[0048] 1. The material for car floor mats provided in the present application has excellent mechanical and wear-resistant properties while ensuring good high-temperature stability, aging resistance, corrosion resistance and waterproof properties, which can meet the performance requirements of modern consumers for car floor mat materials and has a very excellent market prospect.
[0049] 2. The modified resin added to the material for automobile mats provided in the present application can greatly improve the mechanical, aging resistance, waterproof and high temperature stability of the automobile mat material. After the modified resin is added to the mat material system, it can play a good guiding role for the added modified nano powder through its long chain and multi-branched structure, greatly improving the extension and dispersion effect of the nano powder in the system, and increasing the steric hindrance between active molecules, greatly delaying the excessive aggregation between them, thereby effectively enhancing the construction strength of the internal system network, forming a dense gel network, and when water molecules and external active molecules penetrate, their movement rate can be greatly reduced, and the contact frequency between them is reduced, thereby playing an excellent waterproof and aging resistance performance during long-term use.
[0050] 3. The modified nanopowder provided in the present application can greatly improve the mechanical, temperature resistance, waterproof and aging resistance of the car mat material. The added modified nanopowder can greatly improve the compatibility between the composite particles and the TPE system through the modification of the surface groups, and through the hydrogen bonding force and van der Waals force between the surface groups and the internal system, it can form powder micropores and play an excellent group connection role, thereby playing a good internal connection support when external forces act.
[0051] 4. The present application provides a material for automobile floor mats. Under the joint action of the modified resin, the modified nanopowder enhances its own flattening and spreading effect within the system, thereby forming a smoother surface on the surface of the material and when the material is used, and increasing the overall content of the surface resin material. The flat and low surface energy surface can greatly reduce the formation speed of the hydration layer on the surface of the material and the integrity of the hydration layer, thereby maintaining excellent waterproofness and aging resistance under the influence of a long period of moisture environment. DETAILED DESCRIPTION
[0052] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0053] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0054] Example 1
[0055] Embodiment 1 The first aspect provides a material for automobile foot pads, wherein the raw materials are, by mass: 52 parts of TPE, 18 parts of copolymer composition, 12.5 parts of modified resin, 20 parts of modified nano powder, 2.2 parts of lubricant, 8 parts of dispersant, 1.1 parts of coupling agent and 15 parts of auxiliary agent.
[0056] TPE is SEBS with a weight average molecular weight of 86,000, which was purchased from Dongguan Gaochuang Plastic Raw Materials Co., Ltd.
[0057] The copolymer composition is a composition of polypropylene and polycarbonate, and the mass ratio of the two is 3.4:0.8.
[0058] The melt index of polypropylene is 1.85 g / 10 min, the test conditions are: 230°C / 2.16 kg, and the corresponding melt index product is purchased from Shanghai Yuanfeng Plastic Technology Co., Ltd.; the melt index of polycarbonate is 17.26 g / 10 min, the test conditions are: 260°C / 2.16 kg, and the corresponding melt index product is purchased from Shenzhen Matt Plastic Products Co., Ltd.
[0059] The preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 4 parts of 2-ethylhexyl acrylate, 8.5 parts of methyl acrylate and 1.2 parts of hydroxyethyl acrylate to an acryloyl chloride solution, introducing nitrogen, adding 0.04 parts of potassium persulfate, and heating to 75°C to react and generate a prepolymer; S2: mixing the obtained prepolymer with 22.5 parts of acrylamide, adding to a mixed solvent consisting of 160 parts of deionized water and 40 parts of methanol, and adding 0.11 parts of potassium persulfate again, and after nitrogen fully replaces the reaction system gas, heating to 85°C and keeping the temperature for reaction for 6 hours to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the modified resin solution.
[0060] The preparation method of the modified nano powder comprises the following steps, calculated by mass: S1: adding 1.25 parts of silicon dioxide and 4.2 parts of talc to 80 parts of DMF solution, adding 1.4 parts of succinic anhydride and 0.42 parts of 3-glycidyltrimethoxysilane, heating to 65°C and keeping the temperature for reaction for 4 hours, filtering, washing, drying and taking out the product after the reaction is completed, to obtain composite particles; S2: adding 3.2 parts of composite particles and 1.68 parts of zinc acetate to a mixed solution consisting of 20 parts of methanol and 60 parts of deionized water, then heating to 65°C and dropping 1.1 parts of dimethylimidazole methanol solution (a total of 15 parts), the dropping time is 1 hour, and then keeping the temperature for reaction for 3 hours; S3: adding 1.2 parts of acetic acid, 2.5 parts of ethanol and 0.55 parts of dicyclopentadiene after the reaction is completed, heating to 75°C and stirring for continuous reaction for 8 hours, after completion, centrifuging and filtering the product, and vacuum drying to obtain the product.
[0061] The average particle size of talc is 0.18 μm; the average particle size of silicon dioxide is 25 nm.
[0062] The lubricant is white mineral oil #5; the dispersant is a composition of epoxy block polyether and C13 isomeric fatty alcohol polyoxyethylene ether, with a mass ratio of 2.2:4.3; C13 isomeric fatty alcohol polyoxyethylene ether is purchased from the E-1302 product sold by Hai'an Guoyun Petrochemical, with a hydroxyl value of 195 mgKOH / g; the epoxy block polyether is purchased from the L64 product sold by BASF, with a weight average molecular weight of 2900.
[0063] The coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.
[0064] The additives are flame retardant, plasticizer and antistatic agent, and the mass ratio of the three is 5:8.5:1.5.
[0065] The flame retardant is triphenyl phosphate; the plasticizer is DOTP; and the antistatic agent is ethoxylated stearamide.
[0066] The second aspect of this embodiment provides a preparation method for the above-mentioned material for automobile floor mats, and the preparation method comprises the following steps: S1: weigh all the required raw materials for use, then add TPE, copolymer composition, modified resin, lubricant and coupling agent into a stirring pot, and stir and mix at a low speed of 60rpm for 55min; S2: add the remaining raw materials, increase the speed to 180rpm and stir for 2h, add the mixed material after stirring to a twin-screw extruder for extrusion and plasticization, and the extrusion temperature is 220℃; S3: water-cooling and granulating the extruded material, sieving and screening, and ventilation and drying in turn to obtain the obtained material.
[0067] Example 2
[0068] Example 2 The first aspect provides a material for automobile floor mats, in which the raw materials are, by mass: 55 parts of TPE, 15 parts of copolymer composition, 15 parts of modified resin, 16.5 parts of modified nanopowder, 2.2 parts of lubricant, 6 parts of dispersant, 1.1 parts of coupling agent, and 15 parts of additives.
[0069] TPE is SEBS with a weight average molecular weight of 86,000, which was purchased from Dongguan Gaochuang Plastic Raw Materials Co., Ltd.
[0070] The copolymer composition is a composition of polypropylene and polycarbonate, and the mass ratio of the two is 3.4:0.8.
[0071] The melt index of polypropylene is 1.85 g / 10 min, the test conditions are: 230°C / 2.16 kg, and the corresponding melt index product is purchased from Shanghai Yuanfeng Plastic Technology Co., Ltd.; the melt index of polycarbonate is 17.26 g / 10 min, the test conditions are: 260°C / 2.16 kg, and the corresponding melt index product is purchased from Shenzhen Matt Plastic Products Co., Ltd.
[0072] The preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 4 parts of 2-ethylhexyl acrylate, 8.5 parts of methyl acrylate and 1.2 parts of hydroxyethyl acrylate to an acryloyl chloride solution, introducing nitrogen, adding 0.04 parts of potassium persulfate, and heating to 75°C to react and generate a prepolymer; S2: mixing the obtained prepolymer with 22.5 parts of acrylamide, adding to a mixed solvent consisting of 160 parts of deionized water and 40 parts of methanol, and adding 0.11 parts of potassium persulfate again, and after nitrogen fully replaces the reaction system gas, heating to 85°C and keeping the temperature for reaction for 6 hours to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the modified resin solution.
[0073] The preparation method of the modified nano powder comprises the following steps, calculated by mass: S1: adding 1.25 parts of silicon dioxide and 4.2 parts of talc to 80 parts of DMF solution, adding 1.4 parts of succinic anhydride and 0.42 parts of 3-glycidyltrimethoxysilane, heating to 65°C and keeping the temperature for reaction for 4 hours, filtering, washing, drying and taking out the product after the reaction is completed, to obtain composite particles; S2: adding 3.2 parts of composite particles and 1.68 parts of zinc acetate to a mixed solution consisting of 20 parts of methanol and 60 parts of deionized water, then heating to 65°C and dropping 1.1 parts of dimethylimidazole methanol solution (a total of 15 parts), the dropping time is 1 hour, and then keeping the temperature for reaction for 3 hours; S3: adding 1.2 parts of acetic acid, 2.5 parts of ethanol and 0.55 parts of dicyclopentadiene after the reaction is completed, heating to 75°C and stirring for continuous reaction for 8 hours, after completion, centrifuging and filtering the product, and vacuum drying to obtain the product.
[0074] The lubricant is white mineral oil #5; the dispersant is a composition of epoxy block polyether and C13 isomeric fatty alcohol polyoxyethylene ether, with a mass ratio of 2.2:4.3; C13 isomeric fatty alcohol polyoxyethylene ether is purchased from the E-1302 product sold by Hai'an Guoyun Petrochemical, with a hydroxyl value of 195 mgKOH / g; the epoxy block polyether is purchased from the L64 product sold by BASF, with a weight average molecular weight of 2900.
[0075] The coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.
[0076] The additives are flame retardant, plasticizer and antistatic agent, and the mass ratio of the three is 5:8.5:1.5.
[0077] The flame retardant is triphenyl phosphate; the plasticizer is DOTP; and the antistatic agent is ethoxylated stearamide.
[0078] The second aspect of this embodiment provides a preparation method for the above-mentioned material for automobile floor mats, and the preparation method comprises the following steps: S1: weigh all the required raw materials for use, then add TPE, copolymer composition, modified resin, lubricant and coupling agent into a stirring pot, and stir and mix at a low speed of 60rpm for 55min; S2: add the remaining raw materials, increase the speed to 180rpm and stir for 2h, add the mixed material after stirring to a twin-screw extruder for extrusion and plasticization, and the extrusion temperature is 220℃; S3: water-cooling and granulating the extruded material, sieving and screening, and ventilation and drying in turn to obtain the obtained material.
[0079] Comparative Example 1
[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that it is applied to automobile foot pad materials, and the raw materials are, by mass, 75 parts of TPE, 10 parts of copolymer composition, 5 parts of modified resin, 18.5 parts of modified nanopowder, 2.2 parts of lubricant, 7.5 parts of dispersant, 1.1 parts of coupling agent, and 15 parts of additives.
[0081] Comparative Example 2
[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that it is applied to automobile foot pad materials, and the raw materials are, by mass, 75 parts of TPE, 25 parts of copolymer composition, 20 parts of modified resin, 6.5 parts of modified nanopowder, 2.2 parts of lubricant, 8 parts of dispersant, 1.1 parts of coupling agent, and 15 parts of additives.
[0083] Comparative Example 3
[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that the copolymer composition is a composition of polypropylene and polycarbonate, and the mass ratio of the two is 4.5:0.1.
[0085] Comparative Example 4
[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of talc is 0.5 μm; and the average particle size of silicon dioxide is 120 nm.
[0087] Comparative Example 5
[0088] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 0.5 parts of 2-ethylhexyl acrylate, 12 parts of methyl acrylate and 0.1 parts of hydroxyethyl acrylate to an acryloyl chloride solution, introducing nitrogen, adding 0.035 parts of potassium persulfate, and heating to 75°C to react and generate a prepolymer; S2: mixing the obtained prepolymer with 25 parts of acrylamide, adding it to a mixed solvent consisting of 160 parts of deionized water and 40 parts of methanol, and adding 0.12 parts of potassium persulfate again, and after nitrogen fully replaces the reaction system gas, heating to 85°C and keeping the temperature for reaction for 6 hours to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the result.
[0089] Comparative Example 6
[0090] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 2 parts of 2-ethylhexyl acrylate, 8.5 parts of methyl acrylate and 5.5 parts of hydroxyethyl acrylate to an acryloyl chloride solution, introducing nitrogen, adding 0.04 parts of potassium persulfate, and heating to 75°C to react and generate a prepolymer; S2: mixing the obtained prepolymer with 15 parts of acrylamide, adding it to a mixed solvent consisting of 140 parts of deionized water and 30 parts of methanol, and adding 0.96 parts of potassium persulfate again, and after nitrogen fully replaces the reaction system gas, heating to 85°C and keeping the temperature for reaction for 6 hours to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the result.
[0091] Comparative Example 7
[0092] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nano powder comprises the following steps, by mass: S1: adding 1.25 parts of silicon dioxide and 4.2 parts of talc to 80 parts of DMF solution, adding 1.4 parts of citric acid and 0.42 parts of KH-550, heating to 65°C and keeping warm for reaction for 4 hours, after the reaction is completed, filtering, washing, drying and taking out the product to obtain composite particles; S2: adding 3.2 parts of composite particles and 1.68 parts of zinc acetate to a mixed solution consisting of 20 parts of methanol and 60 parts of deionized water, then heating to 65°C and dropping 1.1 parts of dimethylimidazole methanol solution (a total of 15 parts), the dropping time is 1 hour, and then keeping warm for reaction for 3 hours; S3: after the reaction is completed, adding 1.2 parts of acetic acid, 2.5 parts of ethanol and 0.55 parts of dicyclopentadiene and heating to 75°C for continuous stirring and reaction for 8 hours, after completion, centrifuging and filtering the product, and vacuum drying to obtain.
[0093] Comparative Example 8
[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nano powder comprises the following steps, by mass: S1: adding 0.45 parts of silicon dioxide and 5.5 parts of talc to 80 parts of DMF solution, adding 0.6 parts of succinic anhydride and 0.15 parts of 3-glycidyltrimethoxysilane, heating to 65°C and keeping warm for reaction for 4 hours, after the reaction is completed, filtering, washing, drying and taking out the product to obtain composite particles; S2: adding 3.2 parts of composite particles and 1.68 parts of zinc acetate to a mixed solution consisting of 20 parts of methanol and 60 parts of deionized water, then heating to 65°C and dropping 1.1 parts of dimethylimidazole methanol solution (a total of 15 parts), the dropping time is 1 hour, and then keeping warm for reaction for 3 hours; S3: after the reaction is completed, adding 1.2 parts of acetic acid, 2.5 parts of ethanol and 0.55 parts of dicyclopentadiene and heating to 75°C for continuous stirring and reaction for 8 hours, after completion, centrifuging and filtering the product, and vacuum drying to obtain.
[0095] Comparative Example 9
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nano powder comprises the following steps, by mass: S1: adding 1.25 parts of silicon dioxide and 4.2 parts of talc to 80 parts of DMF solution, adding 1.4 parts of succinic anhydride and 0.42 parts of 3-glycidyltrimethoxysilane, heating to 65°C and keeping the temperature for reaction for 4 hours, after the reaction is completed, filtering, washing, drying and taking out the product to obtain composite particles; S2: adding 6.5 parts of composite particles and 0.8 parts of zinc acetate to a mixed solution consisting of 20 parts of methanol and 60 parts of deionized water, then heating to 65°C and dropping 0.5 parts of dimethylimidazole methanol solution (a total of 10 parts), the dropping time is 1 hour, and then keeping the temperature for reaction for 3 hours; S3: after the reaction is completed, adding 1 part of acetic acid, 1.5 parts of ethanol and 0.25 parts of dicyclopentadiene and heating to 75°C for continuous stirring and reaction for 8 hours, after completion, centrifuging and filtering the product, and vacuum drying to obtain.
[0097] Performance Evaluation
[0098] Tensile strength: The tensile strength of the materials obtained in the examples and comparative examples was tested with reference to standard GB / T 1039-92. The test values were averaged from 10 tests and recorded in Table 1.
[0099] Tear strength: The tear strength of the materials obtained in the examples and comparative examples was measured with reference to standard ASTM D-1004. The test values were averaged from 10 tests and recorded in Table 1.
[0100] Waterproof test: The moisture permeability of the materials prepared in the embodiments and comparative examples was tested with reference to the standard GB / T 16925-2008. The test values were recorded in Table 1 as the average value of 10 tests.
[0101] Temperature aging test: The materials obtained in the embodiments and comparative examples were prepared into samples of 5 cm × 5 cm × 0.5 cm, and placed in a constant temperature and humidity chamber at 75°C and 75% relative humidity for 48 hours. After 48 hours, the samples were taken out and naturally cooled to room temperature. The samples were observed to see if there were obvious damage, oxidation yellowing, bubbles, or cracks. If so, they were recorded as unqualified, otherwise they were qualified. 50 samples were tested in each group, and the qualified rate was recorded in Table 1.
[0102] Table 1 Performance test results
[0103]
[0104]
[0105] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 9 in terms of waterproof performance, mechanical properties, high temperature resistance and aging resistance. This is mainly due to the combined effect of the modified nanopowder and modified resin added in the present application. Comparative examples 1 to 9, without adopting the correct technical solution, obviously have gaps in the above-mentioned performances, which further proves the necessity of the technical solution defined in the present application for the technical effect of the present application and solving the technical problems.
Claims
1. A material for automobile foot pads, characterized in that: In parts by mass, the raw materials are: 40-60 parts of TPE, 10-25 parts of copolymer composition, 10-15 parts of modified resin, 10-25 parts of modified nano powder, 1-2.5 parts of lubricant, 4-12 parts of dispersant, 0.5-1.5 parts of coupling agent, and 10-20 parts of auxiliary agent; The copolymer composition is a composition of polypropylene and polycarbonate; The mass ratio of polypropylene to polycarbonate is (3-4): (0.5-1.5); The melt index of the polypropylene is 1.5-3 g / 10 min, and the test conditions are 230° C. / 2.16 kg; The melt index of the polycarbonate is 15-20 g / 10 min, and the test conditions are: 260° C. / 2.16 kg; The preparation method of the modified resin comprises the following steps: S1: adding 2-ethylhexyl acrylate, methyl acrylate and hydroxyethyl acrylate to an organic solution, introducing nitrogen, adding an initiator, and heating to 65-80°C to react and generate a prepolymer; S2: mixing the prepolymer with acrylamide, adding a mixed solvent of deionized water and methanol and adding the initiator again, and after nitrogen fully replaces the reaction system gas, heating to 80-95°C and keeping the temperature for reaction for 5-8h to obtain a modified resin solution; S3: taking the modified resin solution into a new container for demulsification, adding acetone for washing, and then filtering, vacuum drying and granulating to obtain the modified resin solution; The mass ratio of 2-ethylhexyl acrylate, methyl acrylate, hydroxyethyl acrylate and acrylamide is (3-5): (6-10): (1-2): (20-30); The preparation method of the modified nano powder comprises the following steps: S1: adding silicon dioxide and talcum powder to a DMF solution, adding succinic anhydride and a silane coupling agent, heating to 60-70°C for a 4-5h heat preservation reaction, filtering, washing, drying and taking out the product after the reaction is completed to obtain composite particles; S2: adding the composite particles and zinc acetate to a mixed solution of methanol and deionized water, then heating to 60-70°C and dropwise adding a methanol solution of dimethylimidazole for 1-1.2h, and then heat preservation for a 2-4h reaction; S3: adding acetic acid, ethanol and dicyclopentadiene after the reaction is completed, heating to 75-85°C and continuously stirring for a reaction of 8-12h, and after completion, centrifuging and filtering the product, and vacuum drying to obtain the product; The mass ratio of the silicon dioxide, talc, succinic anhydride and silane coupling agent is (1-1.5): (4-4.5): (1.2-1.5): (0.3-0.5); The lubricant is white mineral oil or naphthenic oil; The coupling agent is a titanate coupling agent; The auxiliary agent at least includes a flame retardant, a plasticizer and an antistatic agent; The mass ratio of the flame retardant, the plasticizer and the antistatic agent is (5-6): (8-10): (1.5-2).
2. The material for automobile foot pads according to claim 1, characterized in that: The mass ratio of the TPE, copolymer composition and modified resin is (5-5.5): (1.5-2): (1.2-1.5).
3. The material for automobile foot pads according to claim 2, characterized in that: The mass ratio of the TPE, modified nano powder and dispersant is (5-5.5): (1.5-2.2): (0.6-1).
4. The material for automobile foot pads according to claim 3, characterized in that: The TPE is SEBS; the weight average molecular weight of the SEBS is 60,000-120,000.
5. The material for automobile foot pads according to claim 4, characterized in that: The mass ratio of 2-ethylhexyl acrylate, methyl acrylate, hydroxyethyl acrylate and acrylamide is (3-4): (8-9): (1-1.5): (20-25).
6. The material for automobile foot pads according to claim 5, characterized in that: The mass ratio of the composite particles, zinc acetate, dimethylimidazole and dicyclopentadiene is (3-3.5): (1.5-2): (1-1.2): (0.3-0.6).
7. The material for automobile foot pads according to claim 6, characterized in that: The average particle size of the talc powder is 0.1-0.3 μm; the average particle size of the silicon dioxide is 20-50 nm.
8. The material for automobile foot pads according to claim 7, characterized in that: The silane coupling agent is 3-glycidyltrimethoxysilane.
9. The material for automobile foot pads according to claim 8, characterized in that: The dispersant is a composition of epoxy block polyether and C13-C14 isomeric fatty alcohol polyoxyethylene ether; the mass ratio of the epoxy block polyether to the C13-C14 isomeric fatty alcohol polyoxyethylene ether is (2-2.6): (4-4.5).
10. A method for preparing a material for automobile foot pads according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1: weighing all the required raw materials for use, then adding TPE, copolymer composition, modified resin, lubricant and coupling agent into a stirring pot, and stirring and mixing at a low speed of 40-80 rpm for 40-60 minutes; S2: adding the remaining raw materials, increasing the speed to 150-200 rpm and stirring for 1.5-2 hours, adding the stirred mixture into a twin-screw extruder for extrusion and plasticization, and the extrusion temperature is 200-240°C; S3: sequentially subjecting the extruded materials to water-cooling granulation, sieving and screening, and ventilation drying to obtain the obtained material.
Citation Information
Patent Citations
TPE (Thermo Plastic Elastomer) material capable of being recovered after stress and deformation at low temperature, and preparation method and application thereof
CN106995577A
Fluorescent automobile foot pad material and manufacturing method thereof
CN109486085A
Resin composition for non-slip mat, method for producing same, non-slip mat, and method for producing same
CN116157467A
Cited By
Insulation tubular busbar material and preparation method and application thereof
CN120888139A
